CHARACTERISTIC FEATURES OF VARIATIONS IN HF RADIO WAVE PARAMETERS IN THE IONOSPHERE DURING THE COURSE OF THE SOLAR ECLIPSE OF JUNE 21, 2020 OVER THE PEOPLE’S REPUBLIC OF CHINA - L. F. Chernogor; K. P. Garmash; Q. Guo; Y. Luo; V. T. Rozumenko; Y. Zheng (Radio Physics and Radio Astronomy, 2022)
Subject and Purpose. The study of the effect that each new Solar eclipse (SE) has on radio wave characteristics is an actual scientific and technical issue. The purpose of the present work is to analyze the variations in Doppler spectra (DS), Doppler shift of frequency (DSF), and in the reflected wave amplitude (RWA) that were observed during the SE of June 21, 2020 over the People’s Republic of China.